Comparison of the Blood–Brain Barrier Penetration Ability and Anti-Neuroinflammatory Activity of Chromones in Two Types of Agarwood - Mengyuan Yang; Yanan Yuan; Jingfan Wei; Yifei Pei; Yuanfei Niu; Yifan Zhao; Xiangying Kong; Zhijie Zhang (Pharmaceuticals)
Background/Objectives: Agarwood has a good neuroprotective effect and is often used to relieve anxiety and treat insomnia. This study compared the similarities and differences in the chromone components of two types of agarwood. It further investigated the absorption and brain distribution characteristics of these components in rats and their neuroprotective effects mediated through anti-neuroinflammatory pathways. Methods: This study confirmed, through ITS2 barcoding and chloroplast genome analysis, that both the ordinary and Qi-Nan agarwood are derived from Aquilaria sinensis. A comparative analysis of chromones in ethanol extracts derived from ordinary and Qi-Nan agarwood, as well as those capable of penetrating the blood-brain barrier in vivo, was conducted using UPLC-Q-TOF-MS. Subsequently, an in vitro neuroinflammatory model was established via lipopolysaccharide (LPS)-stimulated BV-2 cells to evaluate the anti-neuroinflammatory activity of differential chromones. Results: UPLC-Q-TOF-MS characterization revealed the chromone components in the two types of agarwood: A total of 81 chromone compounds were identified in the ethanol extracts of ordinary agarwood (OAE) (20 THPECs, 42 FTPECs, and 19 BI), while 41 were identified in the ethanol extracts of Qi-Nan agarwood (QNE) (11 THPECs and 30 FTPECs). Pharmacokinetic analysis in rats showed that 14 components from OAE (eight THPECs and six FTPECs) penetrated the rat serum, and 10 of these 14 components penetrated the blood–brain barrier (BBB). Twelve FTPECs from QNE penetrated the rat serum, all of which penetrated the BBB. The total peak area of the total ion current (TIC) was calculated for the samples, and the TIC of the serum was compared to that of the brain tissue from the same rat to roughly estimate the ratio. The results demonstrated that the capability of FTPECs to traverse the blood–brain barrier is substantially superior to that of THPECs. Correspondingly, only FTPECs were detected using DESI-MS imaging; no THPECs were detected in rat brain tissue, and DESI-MS imaging localized FTPECs to neuroanatomic regions (cerebral cortex, thalamus, and hippocampus). In vitro neuroinflammatory assays revealed the superior anti-inflammatory efficacy of QNE over OAE (IL-6/TNF-α suppression, p < 0.05), correlating with its FTPEC-rich composition. Conclusions: Structure–activity relationships identified FTPECs as potent inhibitors of pro-inflammatory cytokines, exhibiting enhanced BBB penetration (blood–brain relative abundance > 1). These findings establish FTPECs as prioritized candidates for CNS-targeted therapeutics, with QNE’s pharmacological superiority attributed to its FTPEC dominance and optimized BBB transit capacity.